Rhetoric of the personal column: the weekly article of Manuel Jabois and Leila Guerriero in “El País” - Gómez-Calderón, Bernardo; Bryan-Rodríguez, Mercedes (Estudios sobre el Mensaje Periodístico, 2023)
In this paper, the authors analyze the characteristics of Leila Guerriero’s and Manuel Jabois’ columnism according to the postulates of the Theory of Argumentation. Applying rhetorical analysis and contemplating the four phases of the persuasive discourse (intellectio, inventio, dispositio and elocutio), the authors determine the similarities and divergences between Jabois and Guerriero. Among the parallelisms both Jabois and Guerriero deal mainly with personal and social issues, frequently resort to ethos, logos, argument by analogy and by authority, and prefer the inductive macro-structure to defend their theses. As for divergences, Jabois deploys a more varied range of topics in his columns, whereas Guerriero uses argumentation by generalization in a greater number of columns and makes profuse use of figurative language, especially metaphors.
Keywords: Column; Rhetoric; Jabois; Guerriero